THE DIGNITY OF LAITY IN VATICAN II AND IN SOME POST-CONCILIAR DOCUMENTS - Neuner, Peter (Asian Horizons, 2015)
Vatican II tried to overcome the negative definition of laity as “nonclergy” and regarded laity as members of the People of God, participating in the priestly, prophetic and kingly office. In their dignity and their apostolate they are equal to the clergy. Nevertheless in Vatican II there are also formulations which seem to underline a former clericalism. These texts were written in order to give the conservative minority of the bishops the chance to subscribe the documents. Compromises were necessary, because councils strive for a consensus. In the years after the Council in western societies there occurred large turbulences and they also affected the Church. Especially the crisis in clergy with a dramatic reduction of young priests led to concerns on the future. Thus post-conciliar Vatican documents on the laity, e.g. Christifideles laici, tried anew, to underline the difference between laity and clergy, they were more interested on priests than on the laity. They picked up just the formulations containing the compromises and interpreted them in a traditionalist way. The essay shows, that in this respect these post-conciliar documents are not in accordance with the Council. It strives torediscover Vatican II and to make its approach fruitful to the Church of today.